Development and psychometric evaluation of the CO-PARTNER tool for collaboration and parent participation in neonatal care - van Veenendaal Nicole R; Auxier Jennifer N; van der Schoor Sophie RD; Franck Linda S; Stelwagen Mireille A; de Groof Femke; van Goudoever Johannes B; Eekhout Iris E; de Vet Henrica CW; Axelin Anna; van Kempen Anne AMW (PUBLIC LIBRARY SCIENCE, 2022)
Background
Active parent participation in neonatal care and collaboration between parents and professionals during infant hospitalization in the neonatal intensive care unit (NICU) is beneficial for infants and their parents. A tool is needed to support parents and to study the effects and implementation of parent-partnered models of neonatal care.
Methods
We developed and psychometrically evaluated a tool measuring active parent participation and collaboration in neonatal care within six domains: Daily Care, Medical Care, Acquiring Information, Parent Advocacy, Time Spent with Infant and Closeness and Comforting the Infant. Items were generated in focus group discussions and in-depth interviews with professionals and parents. The tool was completed at NICU-discharge by 306 parents (174 mothers and 132 fathers) of preterm infants. Subsequently, we studied structural validity with confirmatory factor analysis (CFA), construct validity, using the Average Variance Extracted and Heterotrait-Monotrait ratio of correlations, and hypothesis testing with correlations and univariate linear regression. For internal consistency we calculated composite reliability (CR). We performed multiple imputations by chained equations for missing data.
Results
A 31 item tool for parent participation and collaboration in neonatal care was developed. CFA revealed high factor loadings of items within each domain. Internal consistency was 0.558 to 0.938. Convergent validity and discriminant validity were strong. Higher scores correlated with less parent depressive symptoms (r = -0.141, 95%CI -0.240; -0.029, p = 0.0141), less impaired parent-infant bonding (r = -0.196, 95%CI -0.302; -0.056, p<0.0001), higher parent self-efficacy (r = 0.228, 95%CI 0.117; 0.332, p<0.0001), and higher parent satisfaction (r = 0.197, 95%CI 0.090; 0.308, p = 0.001). Parents in a family integrated care model had higher scores than in standard care (beta 6.020, 95%CI 4.144; 7.895, p<0.0001) and mothers scored higher than fathers (beta 2.103,95%CI 0.084; 4.121, p = 0.041).
Conclusion
The CO-PARTNER tool explicitly measures parents' participation and collaboration with professionals in neonatal care incorporating their unique roles in care provision, leadership, and connection to their infant. The tool consists of 31 items within six domains with good face, content, construct and structural validity.